2021
DOI: 10.31234/osf.io/fyx9e
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Politicized climate science: No evidence for science literacy driving motivated reasoning, or polarized belief-updating in a US national experiment

Abstract: A substantial literature demonstrates public polarization over climate change, particularly among the science literate. The dominant explanation for this phenomenon is that science literacy amplifies directional motivated reasoning, the tendency to interpret evidence such that it confirms desired conclusions. However, the evidence regarding this biasing account of science literacy is inconclusive. The present study tests the biasing account of science literacy in a national survey experiment among the U.S. pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Specifically, interventions targeted at increasing metacognitive accuracy (Elosúa et al, 2013;Zohar & Barzilai, 2013) may provide an effective means to mitigate societal polarization over science. This is encouraging since reducing political polarization is particularly relevant for domains where unified, collective action is required, such as for combating climate change (Brechin, 2016;Harris, 2007), but where prior research has repeatedly demonstrated that simply increasing the accuracy of object-level cognition, such as scientific literacy, or numeracy has limited success in reducing societal polarization, and may in fact even propel a societal divide (Kahan et al, 2012(Kahan et al, , 2017; but see Fischer, Huff & Said, 2021b).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, interventions targeted at increasing metacognitive accuracy (Elosúa et al, 2013;Zohar & Barzilai, 2013) may provide an effective means to mitigate societal polarization over science. This is encouraging since reducing political polarization is particularly relevant for domains where unified, collective action is required, such as for combating climate change (Brechin, 2016;Harris, 2007), but where prior research has repeatedly demonstrated that simply increasing the accuracy of object-level cognition, such as scientific literacy, or numeracy has limited success in reducing societal polarization, and may in fact even propel a societal divide (Kahan et al, 2012(Kahan et al, , 2017; but see Fischer, Huff & Said, 2021b).…”
Section: Discussionmentioning
confidence: 99%